Processos oxidativos avançados na produção de água de reúso a partir de efluente sanitário tratado: remoção de contaminantes emergentes - Ferreira, Josilei da Silva (2022)
ADVANCED OXIDATION PROCESSES IN THE PRODUCTION OF REUSE WATER FROM TREATED SANITARY SEWAGE: REMOVAL OF CONTAMINANTS OF EMERGING CONCERN. One of the great global challenges nowadays is the maintenance of water supply conditions facing the densification of large population centers and the decline in the availability and quality of freshwater springs. This work focused to study strategies aiming the removal of molecules called contaminants of emerging concern. Investigations were carried out in a pilot system provided by steps such as photochemical oxidation, photoperoxidation and filtration through an activated carbon bed, continuosly fed by a MBR effluent, treating sewage. Preliminary bench studies pointed out great efficiency in the removal of the target compounds (carbamazepine, propranolol, atenolol, caffeine, diclofenac and ibuprofen), when in aqueous solution, using photoperoxidation process, reaching removals treatment greatest than 85% for caffeine and more than 95% for the other compounds. However, these studied compounds were resistant to photochemical oxidation, removing only diclofenac (100%), ibuprofen (64%) and propranolol (24%) and have shown resistance to peroxide oxidation, which did not promote the removal of any of the compounds. Despite promoting consistent oxidation, the photoperoxidation process led to the formation of by-products with potential toxicity when assessed by performing tests with lettuce seeds (L. Sativa). Studies carried out in the pilot system included the use of the activated carbon bed filtration process in addition to the processes pre-evaluated in the bench studies. The photolysis process, very similar to what was witnessed on the bench, was also able to remove diclofenac (100%) and, much less effectively, ibuprofen (9%). Oxidation by hydrogen peroxide and photoperoxidation occurred for all compounds in the order of 60.2 to 83.4%, and higher than 97% when filtered in an activated carbon bed.